Effects of Fallow Management Practices on Soil Water, Crop Yield and Water Use Efficiency in Winter Wheat Monoculture System: A Meta-Analysis - Adil, Muhammad; Zhang, Shaohong; Wang, Jun; Shah, Adnan Noor; Tanveer, Mohsin; Fiaz, Sajid (Frontiers in Plant Science, 2022)
Winter wheat monoculture is a predominant cropping system for agricultural production in dry areas. However, fallow management effects on soil water conservation and crop yield and water use have been inconsistent among studies. We selected 137 studies and performed a meta-analysis to test the effects of tillage and mulching during the fallow period on precipitation storage efficiency (PSE), soil water storage at wheat planting (SWSp), crop yield, evapotranspiration (ET), and water use efficiency (WUE). Compared to conventional tillage (CT), conservation tillage during fallow period overall increased PSE, SWSp and wheat yield by 31.0, 6.4, and 7.9%, respectively, but did not affect ET and WUE. No tillage (NT) had a better performance on soil water conservation during fallow period but a similar effect on wheat yield and WUE compared to reduced tillage (RT) and subsoil tillage (ST). Compared to no mulching, fallow mulching practices overall increased PSE by 19.4%, but had a non-significant impact on SWSp, wheat yield, and ET. Compared to straw mulching, film mulching, and stubble mulching during fallow period, cover cropping as a biological mulching decreased SWSp, wheat yield, and WUE significantly. Wheat WUE was improved by straw mulching but not affected by film mulching and stubble mulching. Strong interactions between tillage method and mulching practices were found for most variables. NT with fallow mulching or with no mulching exhibited a greater impact on soil water conservation during fallow period compared to other combinations. The effects of tillage and mulching during fallow period on soil water conservation and wheat yield and water use also varied with soil and climatic conditions. Overall, NT in combination with straw mulching significantly increased SWSp, PSE, wheat yield, and WUE and can be the best fallow management practice for winter wheat production in varying edaphic and climatic conditions.